Gambaran Kualitas Pembelajaran Daring, Pelayanan Akademik, dan Tingkat Kepuasan Mahasiswa di Masa Pandemi COVID-19 - Dita Agustia; Abdul Aziz Hakim; Anindya Mar’atus Sholikhah; Ratna Candra Dewi; Nanda Rimawati (Universitas Negeri Makassar, 2021)
This research aims to evaluate the online lecture process during the pandemic period, as well as measure the level of student satisfaction towards the implementation of online lectures at the Faculty of Sports Science, Universitas Negeri Surabaya. This research was descriptive study with a survey research model. Sample withdrawal was done by purposive sampling method, which determines the class of 2017- 2020 as a research respondent. The student assessment and satisfaction questionnaire were measured using the Likert scale with alternative answers 1 (dissatisfied) to 4 (very satisfied). The data was descriptively analyzed and bivariate using independent t-test and Anova one way tests. A total of 50.5% of students have a good internet conditions. Lack of concentration is the most common problem (28.1%). The next problem is more lectures give students many assignments (17.6%). Overall, students' assessment of the online lecture process during the COVID 19 pandemic was good, While the level of student satisfaction with online lectures in the faculty of sports science is in the satisfied category. This result will be evaluated for lecturers and education personnel to continuously improve the quality of service to students.